1998
DOI: 10.1161/01.cir.97.1.5
|View full text |Cite|
|
Sign up to set email alerts
|

Monitoring Platelet GP IIb/IIIa Antagonist Therapy

Abstract: Platelet GP IIb/IIIa receptor antagonist therapy with abciximab (ReoPro), the Fab fragment of a mouse/ human chimeric version of the murine 7E3 antibody, is currently used to prevent ischemic complications of percutaneous coronary interventions in select cases, and the efficacy and safety of abciximab for other related indications are under study.1-4 A number of low-molecular-weight GP IIb/IIIa antagonists patterned on the arginine-glycine-aspartic acid (RGD) cell recognition sequence have also shown benefit i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
46
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 43 publications
1
46
0
2
Order By: Relevance
“…Experimental and clinical studies have suggested that occupancy of at least 80% of the receptor population and inhibition of platelet aggregation to ADP (5 to 20 micromoles per liter) by at least 80% results in potent antithrombotic effects. 497 The various GP IIb/IIIa antagonists, however, possess significantly different pharmacokinetic and pharmacodynamic properties. 498 Abciximab is a Fab fragment of a humanized murine antibody that has a short plasma half-life but strong affinity for the receptor, which results in some receptor occupancy that persists in part for weeks.…”
Section: Platelet Gp Iib/iiia Receptor Antagonistsmentioning
confidence: 99%
“…Experimental and clinical studies have suggested that occupancy of at least 80% of the receptor population and inhibition of platelet aggregation to ADP (5 to 20 micromoles per liter) by at least 80% results in potent antithrombotic effects. 497 The various GP IIb/IIIa antagonists, however, possess significantly different pharmacokinetic and pharmacodynamic properties. 498 Abciximab is a Fab fragment of a humanized murine antibody that has a short plasma half-life but strong affinity for the receptor, which results in some receptor occupancy that persists in part for weeks.…”
Section: Platelet Gp Iib/iiia Receptor Antagonistsmentioning
confidence: 99%
“…58 Therefore, the discussion of the pharmacodynamic assessment of blood samples from patients undergoing GP IIb/IIIa antagonist therapy will focus on several key issues. The pharmacological effects of GP IIb/IIIa antagonists can be assessed in a number of different ways.…”
Section: Platelet Monitoring: Pharmacodynamic Surrogatesmentioning
confidence: 99%
“…27,36,59,60 Although the relative ease of measuring ex vivo platelet aggregation might suggest that this measurement would be appropriate for these purposes, platelet aggregation is highly variable within patient populations, is highly dependent on the skill and experience of the investigators performing the measurements, and may be affected by preparation and handling of blood samples. 58 Although most laboratories assess the extent of platelet aggregation by the maximal change in percentage of light transmission, it is also possible, and perhaps equally valid, to measure the initial slope of the aggregation response.…”
Section: Platelet Monitoring: Pharmacodynamic Surrogatesmentioning
confidence: 99%
“…The platelet GP IIb/IIIa receptor antagonists act by occupying the receptors, preventing fibrinogen from binding and thereby preventing platelet aggregation. Experimental and clinical studies have suggested that occupancy of 80% or more of the receptor population and inhibition of platelet aggregation to adenosine diphosphate (5 to 20 micromoles per liter) by 80% or more results in potent anticoagulant effects (169).…”
Section: Platelet Gp Iib/iiia Receptor Antagonistsmentioning
confidence: 99%